2019
DOI: 10.3390/plants8040095
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate Distribution in the Aerial Parts of sel1-10, a Disruption Mutant of the Sulfate Transporter SULTR1;2, in Mature Arabidopsis thaliana Plants

Abstract: Plants take up sulfur (S), an essential element for all organisms, as sulfate, which is mainly attributed to the function of SULTR1;2 in Arabidopsis. A disruption mutant of SULTR1;2, sel1-10, has been characterized with phenotypes similar to plants grown under sulfur deficiency (−S). Although the effects of −S on S metabolism were well investigated in seedlings, no studies have been performed on mature Arabidopsis plants. To study further the effects of −S on S metabolism, we analyzed the accumulation and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Although the effects of S deficiency on S metabolism have been well investigated in seedlings, no studies have been performed on mature A. thaliana plants. Morikawa-Ichinose et al (2019) [4] analyzed the accumulation and distribution of S-containing compounds in different parts of mature sel1-10, as well as wildtype (WT) plants grown under long-day conditions. While the levels of sulfate, cysteine, and glutathione were almost similar between sel1-10 and WT, levels of glucosinolates (GSLs) differed depending on plant part.…”
Section: New Insights Into the Effect Of Sulfur Availability On Plantmentioning
confidence: 99%
“…Although the effects of S deficiency on S metabolism have been well investigated in seedlings, no studies have been performed on mature A. thaliana plants. Morikawa-Ichinose et al (2019) [4] analyzed the accumulation and distribution of S-containing compounds in different parts of mature sel1-10, as well as wildtype (WT) plants grown under long-day conditions. While the levels of sulfate, cysteine, and glutathione were almost similar between sel1-10 and WT, levels of glucosinolates (GSLs) differed depending on plant part.…”
Section: New Insights Into the Effect Of Sulfur Availability On Plantmentioning
confidence: 99%
“…AST68, known as sulphate transporter 2;1, is located in the plasma membrane, similar to SULTR1;1 and SULTR1;2. These two TPs are involved in the GSL sulphur-assimilation process that transports sulphate to the Arabidopsis roots [ 39 , 40 ]. The gene expression of SULTR1;1 and SULTR1;2 is significantly increased in Arabidopsis sdi1sdi -knockout lines.…”
Section: Discussionmentioning
confidence: 99%
“…The sulphur uptake in GSL-containing plants suggests a significant role for sulphur in GSL biosynthesis. Metabolomic and transcriptomic studies by Koprivova and Kopriva [ 39 ] and Morikawa-Ichinose et al [ 40 ] found that GSL accumulation was significantly reduced in a sulphur-deficient environment, suggesting a role for sulphur in GSL biosynthesis [ 41 , 42 , 43 ]. SULTR1;1 and SULTR1;2 are sulphate transporters found in Arabidopsis roots, and their expression is increased during sulphur limitation [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several metabolomic and transcriptomic studies reported a significant reduction in GSL accumulation under sulfur deficiency environment, suggesting the role of sulfur in GSL biosynthesis ( Nikiforova et al, 2003 ; Hirai et al, 2003 ; Aarabi et al, 2016 ). SULTR1; 1 and SULTR1; 2 in Arabidopsis roots play a role as sulfate transporters and their expression was increased in sulfur-limitation Arabidopsis ( Koprivova & Kopriva, 2014 ; Morikawa-Ichinose et al, 2019 ). The molecular components involving sulfate and GSL transport machinery is more complex in Brassica crops, and requires an in-depth understanding on the GSL mechanism.…”
Section: Discussionmentioning
confidence: 99%